Tocotrienol-rich Palm Oil Extract Induces NAD(P)H:quinone Oxidoreductase 1 (NQO1) Expression in Mice Liver - Ahmed Atia & , Nadia Alrawaiq, Azman Abdullah (Journal of Applied Pharmaceutical Science, 2016)
A diet rich in tocotrienols has been shown to be beneficial for health. However, its detailed mechanism of action is still not fully understood. NAD(P)H:quinone oxidoreductase 1 (NQO1) is important in cellular defence due to its ability to detoxify reactive quinones and quinoneimines to their less toxic hydroquinones forms. The objective of this study is to investigate the effects of different doses of palm oil-derived tocotrienol rich fraction (palm TRF) supplementation on NQO1 gene and protein expression in mice livers. Western blot and qPCR assays were used to detect NQO1 expression levels. It was found that palm TRF significantly induced NQO1 expression at all doses given. In conclusion, palm TRF treatment increased NQO1 gene and protein expression in mice liver dose dependently, with the highest expression seen in mice treated with 1000 mg/kg palm TRF, followed by 500 and 200 mg/kg respectively.
Keywords: Gene expression, NQO1, palm oil, tocotrienol rich fraction, vitamin E.